Application of the Nazariyah Wahdah Approach to Increase Interest in Learning Arabic for High School Students in Sidoarjo Regency - Nurin Fera; Najih Anwar (Universitas Muhammadiyah Sidoarjo, 2022)
Problem in this study is, first, how is the application of the Nazariyah Wahdah Approach to learning Arabic in class XI Language at SMA Muhammadiyah 3 Tulangan Sidoarjo?. Second, how much is the increase in students' interest in learning Arabic using the Nazariyah Wahdah approach in class XI Language at SMA Muhammadiyah 3 Tulangan Sidoarjo?. The methodology applied in this research is Classroom Action Research, with the type of participant. The results show that the application of the Nazariyah Wahdah approach is carried out by taking one material that includes all 4 Arabic skills, namely listening skills, speaking skills, reading skills, and writing skills, as well as 3 elements in Arabic, namely Ashwat, Mufradat and Qawaid. While the increase in interest in learning Arabic states that, in the pre-cycle students who are interested are 64.89% in the less interested category. Then after being given action in the first cycle, students who were interested increased by 67.16% with the same category, less interested. In the second cycle there was an increase in interest in learning Arabic as much as 68.01% and it was included in the moderately interested category. In cycle III, there was an increase of 70.63% with the same category, which was quite interested. So, based on the results of the questionnaire from pre-cycle to cycle III, it is evident that the Nazariyah Wahdah approach can increase interest in learning Arabic for class XI students from the category of less interested to moderately interested with an average of 70.63%.